Drug Delivery: Photosensitizer‐Incorporated Quadruplex DNA‐Gated Nanovechicles for Light‐Triggered, Targeted Dual Drug Delivery to Cancer Cells (Small 16/2013). Issue 16 (16th August 2013) - Chen, Cuie; Zhou, Li; Geng, Jie; Ren, Jinsong; Qu, Xiaogang
<x xml:space="preserve">Abstract</x> A light‐operated vehicle for targeted intracellular drug delivery has been constructed by J. Ren, X. Qu, and co‐workers using photosensitizer‐incorporated G‐quadruplex DNAcapped mesoporous silica nanoparticles. Upon light irradiation, the photosensitizer generates reactive oxygen species, causing the DNA capping to be cleaved and allowing the cargo (drugs) to be released. This platform, described in detail on page 2793, makes it possible to develop a drug‐carrier system for a synergistic combination of chemotherapy and photodynamic therapy for the treatment of cancer with a high spatial/temporal control. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>